Obtaining continuous BrAC/BAC estimates in the field: A hybrid system integrating transdermal alcohol biosensor, Intellidrink smartphone app, and BrAC Estimator software tools. (August 2018) - Luczak, Susan E.; Hawkins, Ashley L.; Dai, Zheng; Wichmann, Raphael; Wang, Chunming; Rosen, I.Gary
Abstract: Biosensors have been developed to measure transdermal alcohol concentration (TAC), but converting TAC into interpretable indices of blood/breath alcohol concentration (BAC/BrAC) is difficult because of variations that occur in TAC across individuals, drinking episodes, and devices. We have developed mathematical models and the BrAC Estimator software for calibrating and inverting TAC into quantifiable BrAC estimates (eBrAC). The calibration protocol to determine the individualized parameters for a specific individual wearing a specific device requires a drinking session in which BrAC and TAC measurements are obtained simultaneously. This calibration protocol was originally conducted in the laboratory with breath analyzers used to produce the BrAC data. Here we develop and test an alternative calibration protocol using drinking diary data collected in the field with the smartphone app Intellidrink to produce the BrAC calibration data. We compared BrAC Estimator software results for 11 drinking episodes collected by an expert user when using Intellidrink versus breath analyzer measurements as BrAC calibration data. Inversion phase results indicated the Intellidrink calibration protocol produced similar eBrAC curves and captured peak eBrAC to within 0.0003%, time of peak eBrAC to within 18 min, and area under the eBrAC curve to within 0.025% alcohol–hours as the breath analyzer calibration protocol. This study provides evidence that drinking diary data can be used in place of breath analyzer data in the BrAC Estimator software calibration procedure, which can reduce participant and researcher burden and expand the potential software user pool beyond researchers studying participants who can drink in the laboratory. Graphical abstract: Image 1 Highlights: Data from transdermal alcohol biosensors need to be converted into interpretable quantitative estimates of alcohol levels. We created a simplified calibration procedure for the BrAC Estimator software using drinking diary data. This novel hybrid software system makes it possible to obtain estimated BrAC from transdermal data without laboratory data. The software system will make it possible for clinicians and lay individuals to monitor estimated BrAC levels in the field.